Factors affecting beta in manufacturing companies in Indonesia Stock Exchange - Retnoning Ambarwati (Profesional Muda Cendekia Publishing, 2020)
This research has want to know and prove the effect of dividend payout, asset growth, asset size, liquidity, financial leverage, earning variability and accounting beta to beta of stock simultaneously and partially in manufacturing companies at Jakarta Stock Exchange. This research use secondary data which is collected based on time series data and cross section include 12 manufacturing company stocks as the sample. The data is collected from the online data of Jakarta Stock Exchange in YPKP, Indonesia Capital Market Directory, JSX Statistic, and Business News. The model of this research is estimated by Generalized Least Square (GLS) with Fixed Effect Model and Dummy Variable to estimate the effect of some financial variables specifically towards Beta of Stock. The result show that all of the variables in this research consistent with the theory as expected. The coefficient direction of asset growth, financial leverage, earning variability and accounting beta shows positive, while the coefficient direction of dividend payout, asset size, liquidity shows oppositely. Simultaneously all variables influence beta of stock, in the other side partially shows that asset growth, earning variability, asset size, and liquidity, have significant effect to beta, whereas dividend payout ratio, financial leverage and accounting beta do not have significant effect. One of the implications of this research is that the study of beta of stock should be more comprehensively, not only contains micro variables but also the macro variables as well include dimension of social economy and politic